PENGARUH INFLASI DAN UPAH MINIMUM KOTA (UMK) TERHADAP TINGKAT PENGANGGURAN TERBUKA DI KOTA PADANG SIDEMPUAN - Nabila Nabila; Noni Rozaini (Niagawan, 2022)
This study aims to determine how the effect of inflation and the municipality minimum wage on the open unemployment rate in Padang Sidempuan City in 2006-2020. The type of research used in this study is quantitative research and uses secondary data with a time series type. The source of data in this study is the official website of the Badan Pusat Statistik (BPS). The analytical method used in this study is multiple linear regression analysis, which is processed using the E-views 10 program. The results of this study indicate that partially inflation has a positive and insignificant effect on the unemployment rate with a significance value of 0.8990. The municipality minimum wage  has a negative and significant effect on the open unemployment rate with a significance value of 0.0002. And simultaneously inflation and the municipality minimum wage have a significant effect on the open unemployment rate with a significance value of 0.000076 and the independent variables of inflation and the municipality minimum wage have an effect of 79.40% on the open unemployment rate in Padang Sidempuan City.